Microbial Biotechnology Volume 2. Application in Food and Pharmacology (Springer Singapore, 2018)
This edited book, is a collection of 25 chapters describing the recent advancements in the application of microbial technology in the food and pharmacology sector. The main focus of this book is application of microbes, food preservation techniques utilizing microbes, probiotics, seaweeds, algae, enzymatic abatement of urethane in fermentation of beverages, bioethanol production, pesticides, probiotic biosurfactants, drought tolerance, synthesis of application of oncolytic viruses in cancer treatment, microbe based metallic nanoparticles, agro chemicals, endophytes, metabolites, antibiotics etc. This book highlighted the significant aspects of the vast subject area of microbial biotechnology and their potential applications in food and pharmacology with various topics from eminent experts around the World. This book would serve as an excellent reference book for researchers and students in the Food Science, Food Biotechnology, Microbiology and Pharmaceutical fields.